Literasi Wirausaha Pada Inovasi Produk Untuk Meningkatkan Nilai Ekonomi (Studi Produk Kelapa Pada Masyarakat Rejing Tiris Probolinggo) - Aulia, Irma; Mohammad Syaiful Suib (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2023)
This research aims to provide the community with an understanding of innovation in entrepreneurship in products in Rejing Village to improve their economy. Understanding of the economic value of coconut products is still minimal, in fact there is no use of coconuts for various products such as oil, drinks, fertilizer, crafts and so on. The method used is descriptive qualitative with a case study approach. Data collection techniques through observation, interviews, documentation and literature study. Primary data sources are village heads, communities that have coconut trees and secondary data is in the form of literature studies. The results of this research are that the community in this village still has minimal understanding of the potential that can be developed in coconut products, this is due to minimal literacy regarding the potential of coconut, the community is in a hurry to make a profit from direct sales of coconut and the community is still focused on fulfilling primary needs in other sectors such as planting teak trees and sengon trees. Digital literacy is also a very important medium in marketing digitally to increase the economic value of society and large market power in a wider reach.